Advances in Membrane Technology: A Comprehensive Review of Materials, Processes, and Applications - Kulsum Jamal (International Journal of Membranes, 2025)
Membrane technology has become a critical platform for sustainable separation processes across water treatment, energy generation, chemical processing, and healthcare. Over recent decades, advances in materials, fabrication methods, and process design have dramatically expanded the performance, efficiency, and applications of membrane-based systems. Polymeric membranes dominate the industry due to cost-effectiveness and scalability, while ceramic, metallic, and composite membranes offer enhanced thermal and chemical resistance for specialized environments. Nanostructured and bio-inspired membranes, incorporating materials such as graphene oxide, carbon nanotubes, and functionalized polymers, are transforming the landscape with improved selectivity, permeability, and fouling resistance. Innovations in fabrication techniques, including phase inversion, interfacial polymerization, electrospinning, and additive manufacturing, have enabled membranes with finely tuned properties. Simultaneously, processes such as reverse osmosis, nanofiltration, forward osmosis, membrane distillation, and membrane bioreactors have achieved greater efficiency and broader industrial uptake. Applications span water and wastewater treatment, carbon capture, fuel cells, pharmaceuticals, and food processing. Despite these achievements, challenges including fouling, cost, material stability, and energy consumption persist. This review provides a comprehensive overview of recent advances in membrane technology, focusing on materials, processes, and applications. It highlights current challenges and future opportunities in sustainable design, smart membrane development, and integration with emerging technologies such as nanotechnology and artificial intelligence.
Keywords: Nanostructured Membranes; Water treatment; membrane technology; separation processes; sustainable design